Analisis Yuridis Pelimpahan Wewenang Delegasi dalam Kasus Penandatanganan Izin Usaha Oleh Kepala Dinas Sebagai Kuasa Bupati - Hikmatul Hasana; Firman Octhaviana Sulistiyono (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study analyzes the juridical implications of delegated authority in the context of business license signing by heads of regional offices acting on behalf of regents. Using a qualitative approach with library research, the paper explores the legal foundation, validity, and administrative consequences of delegation within local governance. The findings indicate that delegation of authority is a legitimate administrative mechanism recognized under Indonesian law, particularly within Law No. 23 of 2014 concerning Regional Government. However, its implementation frequently lacks procedural clarity, leading to potential legal defects (ultra vires) in administrative decisions. The study emphasizes that the validity of business permits depends on both formal and substantive fulfillment of delegation requirements through explicit legal instruments such as regional head decrees. Improper delegation not only invalidates administrative acts but also undermines legal certainty and public trust in local governance. Theoretically, this research contributes to strengthening the doctrine of state administrative legality, while practically, it provides recommendations for standardizing delegation mechanisms to enhance transparency, accountability, and legal compliance in regional public service delivery.